Triggering the Generation of an Iron(IV)-Oxo Compound and Its Reactivity toward Sulfides by Ru(II) Photocatalysis - Company, Anna (American Chemical Society, 2014)
[Image: see text] The preparation of [Fe(IV)(O)(MePy(2)tacn)](2+) (2, MePy(2)tacn = N-methyl-N,N-bis(2-picolyl)-1,4,7-triazacyclononane) by reaction of [Fe(II)(MePy(2)tacn)(solvent)](2+) (1) and PhIO in CH(3)CN and its full characterization are described. This compound can also be prepared photochemically from its iron(II) precursor by irradiation at 447 nm in the presence of catalytic amounts of [Ru(II)(bpy)(3)](2+) as photosensitizer and a sacrificial electron acceptor (Na(2)S(2)O(8)). Remarkably, the rate of the reaction of the photochemically prepared compound 2 toward sulfides increases 150-fold under irradiation, and 2 is partially regenerated after the sulfide has been consumed; hence, the process can be repeated several times. The origin of this rate enhancement has been established by studying the reaction of chemically generated compound 2 with sulfides under different conditions, which demonstrated that both light and [Ru(II)(bpy)(3)](2+) are necessary for the observed increase in the reaction rate. A combination of nanosecond time-resolved absorption spectroscopy with laser pulse excitation and other mechanistic studies has led to the conclusion that an electron transfer mechanism is the most plausible explanation for the observed rate enhancement. According to this mechanism, the in-situ-generated [Ru(III)(bpy)(3)](3+) oxidizes the sulfide to form the corresponding radical cation, which is eventually oxidized by 2 to the corresponding sulfoxide.